The impact of an enlightenment program on community perception towards children with epilepsy - Komomo Ibor, Eyong; E. Emmanuel, Ekanem; Asindi, Asindi A.; Torty, Chimaeze; E., Brown-Abang (International Journal of Research in Medical Sciences, 2018)
Background: Epilepsy is associated with social stigma and discrimination which is often harmful and devastating. Lack of knowledge and misconception is responsible for these negative attitudes. Public awareness and education are known to improve perception towards epileptics. Methods: A sensitization workshop among community leaders on epilepsy was carried out in a rural community in Cross River State, Nigeria. A pretest questionnaire was administered to participants based on items related to knowledge and perception towards epileptics. The respondents were offered a 2-hour workshop on the causes, types, cure and myths about epilepsy. The same questionnaire was again applied after the workshop. The responses before and after intervention were compared using the McNemar test statistic, with a significance level at p<0.05. Results: Seventy-two respondents participated in the study comprising of 42 (58.3%) males and 30 (41.7%) females. Twenty-eight (38.9%) had primary education and the same number had tertiary education. There was a positive correlation between level of education and performances in the perception towards various domains of epilepsy. Statistical significant differences were found in perceptions regarding cure, mode of contracting epilepsy and potentials of epileptics. However, no statistical difference in perception after the intervention regarding marriage to epileptics. Conclusions: Respondents with higher level of education demonstrated significantly better awareness and attitude towards epileptics compared to those with lower levels the intervention package produced a significant improvement in most domains of perception about epilepsy. Public enlightenment is effective in reducing social stigma and discrimination. It should be encouraged to curtail the negative attitude and perception towards epileptics.